INDONESIAN-UNITED STATES DEFENSE COOPERATION IN THE PRESIDENT JOKO WIDODO ERA - Annidya Indirasari (Pena Wimaya, 2022)
Indonesan and the United States during the presidency of Joko Widodo from 2014 to 2019 as folows: Defense Cooporation In Arrangement of Capacity Building, Joint Exercise Of Indonesia And The United States; Military Law Workshop; Indonesia-US Security Dialogue (UISSD) XII On 1-2 September 2015; Defense Corporation Between Indonesia And The United States Under Confidence Building Measures (CBM) arragement; Bilateral Cooperation State Visit Between Indonesia an The United States; Cooperation Between The Defense Industry, The Transfer Of Conventional Weaponns; Education and Training. The factors are driving Indonesia’s Coorporation with The United States are: The long history of good reations both Indonesia and The United States; the same counter terrorism mission; while the inhibing factor is Indonesia’s preparation; both in terms of human resources or the system that Indonesia has, and there are also obstaces from The United States side, such as the goverment contuning to expain that the US cannot intervene in thecnology transfer process since the authority held by the corporatin, therefore the purchasing and selling process is strictly business to bussines.